Pharmacological treatment of apathy in Lewy body disorders: A systematic review. (March 2019) - Liu, Jennifer; Cooper, Christine A.; Weintraub, Daniel; Dahodwala, Nabila
Abstract: Introduction: There are no approved treatments for apathy, a frequent and incapacitating symptom in Parkinson's disease (PD) and dementia with Lewy bodies (DLB). We reviewed the literature on the pharmacological treatment of apathy in PD and DLB to inform practice and future research. Method: We searched PubMed and PsycINFO using the terms "apathy", "treatment", and "Parkinson" or "Lewy body (bodies)." The results were filtered for "clinical trials" and "case reports." We included articles if apathy was measured as an outcome measure, before and after treatment. References of included articles were also reviewed. Results: The PD search identified 19 articles: 13 randomized control trials (RCTs), 4 open-label studies, 1 case series, and 1 case report. Apathy was the primary outcome in 11 out of 19 studies. A decrease in apathy ratings was seen in 14 of the 19 studies. Of these 14 studies, 9 investigated medications with some dopaminergic effect. Three investigated acetylcholinesterase inhibitors (AChEIs) and found benefit in improving apathy. The DLB search identified 4 articles: 1 RCT, 2 open-label studies, and 1 case series. All 4 studies demonstrated decreased apathy and investigated AChEIs. Conclusions: We identified 23 studies that assessed the pharmacological treatment of apathy. In PD, agents with dopaminergic activity were the most studied and appeared to have the most benefit. AChEIs also appeared to have benefit in both PD and DLB but were less studied. Future studies of apathy treatment would benefit from larger samples and standardized assessments of apathy to define study populations and endpoints. Highlights: Apathy in Lewy body disorders is a common cause of disability and caregiver burden. A systematic review of pharmacological treatments of apathy found 23 studies. There was weak evidence that acetylcholinesterase inhibitors are effective in Lewy Body disorders. There was weak evidence that acetylcholinesterase inhibitors are effective in Parkinson's disease and Dementia with Lewy bodies. Overall, data were limited by study design, sample size and variable apathy assessments.